Seed banks in slash and burn agriculture production systems in Marapanim, Pará - Leal, Eliane Constantinov; Vieira, Ima Célia Guimarães; Kato, Maria do Socorro Andrade (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2006)
In slash-and-burn agriculture, secondary forest has a main role in the fertilization of the soil, after the burning of its plant biomass. Generally, successive burns tend to destroy all forms of regeneration, including the seed banks. With this problem in mind, the Studies of Human Impact on Forests and Floodplains in the Tropics Project (SHIFT), in which this research is inserted, after a series of basic studies on secondary forests in the region of Bragança, has been developing an alternative agricultural production in which secondary forest is used as a source of nutrients and organic matter for the soil in ‘fire-free’ agricultural production systems. The work was developed in the municipality of Marapanim, it was a participative experiment, a new project approach, where the farmers chose the areas. The objective of the present work was to assess the potential of the seed bank in areas subjected to different forms of soil management, characterizing qualitative and quantitatively. The hypothesis that fire diminishes the potential of seed banks and creates favorable conditions for the regeneration of invading herbaceous species was tested, as well as that chopped mulch minimizes the impacts caused by burning on plant diversity and increases the regeneration of biomass-accumulating species. The germination potential of seed banks in the treatments was monitored during 270 days. Density, species richness, families and predominating life forms were assessed in the treatments burn, chopped mulch. In the seed bank before soil management, the average density in burn was 284 individuals/m2 and in the chopped mulch it was 328 individuals/m2, and after soil management in burn there were in average 23 individuals/ m2 found and in the chopped mulch 139 individuals/m2. The most frequent species at both moments and treatments were Borreria latifolia, Fimbristylis meliacea and Cyperus diffusus. The families Cyperaceae, Rubiaceae and Poaceae appeared in high frequency in all areas and in both treatments. In addition, the families Euphorbiaceae, Melastomataceae, Malvaceae, Lamiaceae. Scrophulariaceae and Asteraceae stood out. The most common forms of life found in the treatments were herbs. The different treatments, affected the abundance and floristical richness decreasing the number of seeds of tree and shrub species, which are biomass accumulating.